Optimizing Commenting Ethics on Social Media: “Efforts to Create a Positive Digital Environment" - Eka Miftahul Jannah; Kukuh Rahmat Priono; Mei Aditya Pratiwi Saragih; Nurhasnaini; Agus Salim; Syafira Purba Kinanthi (Commsphere: Jurnal Mahasiswa Ilmu Komunikasi, 2024)
As the use of social media platforms increases, unethical commenting often leads to conflict and creates a hostile atmosphere in cyberspace. Optimizing the ethics of commenting on social media is essential to creating a positive digital environment. This socialization activity aims to build a digital communication culture that is more civilized, respectful, and beneficial to all—creating a positive social media space where every comment is a reflection of wisdom and empathy as a user. The methods used are talk, games, and focus group discussions regarding the ethics of commenting on social media. This event was attended by 30 Dasawisma XVI mothers aged 30-40 years. This activity results in Dasawisma XVI mothers actively using social media to understand and continue to practice valuable things in their comments. This results from Mrs. Rini conveying messages and impressions as Chair of Dasawisma XVI. The Dasawisma XVI mothers can also properly sort through or use media and behave appropriately if there is a risk of encountering hoaxes or false news. Keywords: Social Media, Ethics, Comment, Digital Environment, Communication Culture